The Role of Artificial Intelligence in the Sustainability of Marketing Activities: Control of Digital Marketing Activities and Digital Analytics - Todorovic, Brankica (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The control of digital marketing activities plays a central role in strategic management, ensuring the alignment of marketing initiatives with organizational objectives and long-term sustainability goals. In recent years, digital marketing control has increasingly been operationalized through advanced digital analytics tools, which are further enhanced by artificial intelligence (AI) technologies. The integration of AI enables more accurate monitoring and evaluation of marketing campaign performance, supports advanced levels of personalization, and facilitates real-time, data-driven decision-making, thereby improving both operational efficiency and strategic effectiveness. Despite the growing body of research on digital marketing analytics and AI applications, there remains a limited understanding of how AI-based tools specifically contribute to the control function of digital marketing and how these contributions translate into sustainability and competitive performance outcomes. This paper adopts a descriptive-analytical research approach, drawing on a comprehensive review of relevant academic and professional literature in the fields of digital marketing, digital analytics, marketing control, and AI. Furthermore, the study employs a case study analysis based on multiple approach of selected companies that apply AI-based tools in the control of digital marketing activities.